Elevated levels of calpain 14 in nasal tissue in chronic rhinosinusitis. Issue 3 (17th August 2020) - Boruk, Marina; Dabo, Abdoulaye J.; Nath, Sridesh; Zahid, Kanza; Ploszaj, Magdalena; Wu, Derek; Rosenfeld, Richard; Foronjy, Robert F.; Geraghty, Patrick
Recently, calpain (CAPN) 14 was identified by a genome-wide genetic association study to play a role in eosinophilic oesophagitis [1]. CAPN14 expression is also linked with asthma and allergy sensitivity [2]. The overexpression of CAPN14 impairs epithelial barrier function and CAPN14 expression is triggered by Th2-associated signalling, such as interleukin (IL)-13 and IL-4 [3]. CAPNs are intracellular regulatory proteases, and there are 16 members of the human CAPN family. CAPNs perform a number of functions, including cytoskeletal and membrane proteins restructuring, signal transduction and inactivating enzymes involved in cell cycle progression, gene expression and apoptosis [4]. Therefore, our group performed a small pilot study to investigate CAPN gene expression profiles in tissue from another disease associated with eosinophilia and epithelial barrier function, chronic rhinosinusitis (CRS) [5]. Sinusitis is a condition associated with inflammation in the paranasal sinuses and contiguous nasal mucosa and ∼30 million adults report sinusitis symptoms annually in the United States [6]. Sinusitis is deemed chronic if symptoms persist more than 3 months, with most episodes of sinusitis associated with viral upper respiratory tract infections, asthma, allergic rhinitis and exposure to environmental factors, such as cigarette smoke [7]. Steroids are effective in treating sinusitis, thereby underlining the importance of inflammation in disease pathophysiology, with inflammatory cells such as eosinophils linked to nasal polyps formation that contribute to nasal obstruction [8]. Sinusitis is a common condition associated with inflammation in the sinuses and nasal mucosa. Calpain 14 is highly expressed in the nasal tissues of sinusitis subjects. Calpain 14 is associated with epithelial barrier disruption. https://bit.ly/3fyAwVO